2010
DOI: 10.1088/0004-637x/726/2/57
|View full text |Cite
|
Sign up to set email alerts
|

THE BULK OF THE BLACK HOLE GROWTH SINCEz∼ 1 OCCURS IN A SECULAR UNIVERSE: NO MAJOR MERGER-AGN CONNECTION

Abstract: What is the relevance of major mergers and interactions as triggering mechanisms for active galactic nuclei (AGN) activity? To answer this long-standing question, we analyze 140 XMM-Newton-selected AGN host galaxies and a matched control sample of 1264 inactive galaxies over z ∼ 0.3-1.0 and M * < 10 11.7 M ⊙ with high-resolution HST /ACS imaging from the COSMOS field. The visual analysis of their morphologies by 10 independent human classifiers yields a measure of the fraction of distorted morphologies in the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

33
272
2
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 350 publications
(311 citation statements)
references
References 139 publications
33
272
2
2
Order By: Relevance
“…Bessiere et al (2012), however, find QSOs at several stages of the merging process even before the final merger. On the other hand, Cisternas et al (2011) show that AGNs do not lie in more disturbed hosts and conclude that mergers are not necessarily responsible for nuclear activity. Teng et al (2012) search for double QSOs in pairs of galaxies where one member is already known to host an AGN and find only one such case out of twelve objects.…”
Section: Discussionmentioning
confidence: 86%
“…Bessiere et al (2012), however, find QSOs at several stages of the merging process even before the final merger. On the other hand, Cisternas et al (2011) show that AGNs do not lie in more disturbed hosts and conclude that mergers are not necessarily responsible for nuclear activity. Teng et al (2012) search for double QSOs in pairs of galaxies where one member is already known to host an AGN and find only one such case out of twelve objects.…”
Section: Discussionmentioning
confidence: 86%
“…At low redshifts, we compare with the PG quasar sample of Dunlop et al (2003); Floyd et al (2004) (we plot the fraction with best-fit bulge-to-total mass ratio B/T < 0.5 in bins of Lbol, estimated from the observed nuclear Vband luminosities, with Poisson errors). At z ∼ 0.5 − 1, we compare the low-luminosity sample from COSMOS studied in Gabor et al (2009) and Cisternas et al (2011); we plot the "final" quoted fraction of disk-dominated galaxies in the sample (with the approximate ∼ 10% systematic difference between classifiers quoted therein) and 90% range of Lbol estimated from the hard X-ray luminosities. We also compare the sample of true quasars in Zakamska et al (2006Zakamska et al ( , 2008; Liu et al (2009) at z ∼ 0.3 − 0.7.…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, recent observations of AGN host morphologies and colors have suggested that major mergers probably do not fuel most low and intermediate-luminosity AGN, as a large fraction appear in "normal" disks (Gabor et al 2009;Schawinski et al 2011;Cisternas et al 2011;Kocevski et al 2012;Rosario et al 2011;Civano et al 2012;Santini et al 2012;Mullaney et al 2012;Treister et al 2012). This should perhaps not be surprising.…”
Section: Introductionmentioning
confidence: 99%
“…The discovery of double AGNs (e.g., Hennawi et al 2010;McGurk et al 2011) adds support to a merger origin of the AGN activity. On the other hand, various observational studies suggest that moderately luminous AGN are typically not major-merger-driven at z < ∼ 1 (Salucci et al 1999;Grogin et al 2005;Pierce et al 2007;Georgakakis et al 2009;Cisternas et al 2011;Villforth et al 2014), and interestingly also at z ≈ 2 (Rosario et al 2013a;Silverman et al 2011;Kocevski et al 2012). Bournaud et al (2012) find a correlation between the presence of violent instabilities and AGN activity in gas-rich galaxies at high redshift, thanks to the presence of giant clumps of gas in the disk.…”
Section: Introductionmentioning
confidence: 99%